Study on Coconut in India - Committee on Natural Resources Planning Commission (Committee on Natural Resources Planning Commission Government of India, 1963)
This summary presents the key findings of a Planning Commission–sponsored study on coconut cultivation and coconut oil production in India, highlighting the crop’s economic significance and strategic importance. Despite being one of the world’s largest coconut producers, India remains dependent on imports of copra and coconut oil due to rising domestic demand, particularly from edible and industrial uses. The study examines regional production patterns, ecological requirements, expansion potential, and trade dynamics, with special emphasis on Kerala and other southern states. It recommends systematic area surveys, expansion of nursery programs, improved agronomic practices, quality control measures, and complementary development of palm oil cultivation to reduce import dependence. Collectively, the findings provide a policy-oriented framework for strengthening the coconut sector and achieving greater self-sufficiency under the Fourth Five-Year Plan and beyond.
Committee on Natural Resources Planning Commission New Delhi 1963
Keywords: Coconut Cultivation; Coconut Oil Production; Copra Trade; Plantation Crops; Regional Production Patterns; Palm Oil Substitution; Agricultural Expansion; Nursery Development; Quality Control Measures; Fertilizer Use; Trade Policy; Fourth Five-Year Plan